Efek kecepatan udara dan penambahan serbuk kayu terhadap kadar kelembapan kotoran sapi yang dikeringkan menggunakan mesin pengering tipe drum dryer - Harmiansyah; Kardiansyah; Lathifa Putri Afisna; Teuku Meurah Indra Riayatsyah; Rustam Efendi (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Indonesia is a tropical country where farmers and ranchers make up the majority of the population. Cows are one form of livestock bred, and the negative impact is air pollution created by cow manure. Drying cow dung with a dryer (drum drayer) is a very effective way to remove the stink that comes from it. The goal of this study was to see how air velocity and powder administration affected moisture content and water evaporation rate when drying cow dung in a drum dryer. This study employed an experimental method, recording temperature changes every 10 minutes for 30 minutes. Moisture levels should be measured and compared before and after heating with different blower speeds (1.3 m/s, 1.7 m/s, 1.9 m/s, and 2.4 m/s). The results revealed that the rate of water evaporation differed depending on the air velocity change. At an air speed of 2.4 m/s, the highest water evaporation rate is 0.000736 kg/s, while the lowest water evaporation rate is 0.000142 kg/s. The comparison of moisture content from the drying process with and without sawdust revealed values that were not significantly different. The ultimate moisture content attained at an air speed of 2.4 m/s is 70%, which is 5% higher than the drying procedure without powder (final moisture value is 75%). However, at a speed of 1.3 m/s, the final moisture content value obtained is 90%, which is higher than the final moisture content value acquired during the drying process without powder (80%).